2017
DOI: 10.1002/cpe.4069
|View full text |Cite
|
Sign up to set email alerts
|

Hardware‐assisted software event tracing

Abstract: Summary Event tracing is a reliable and a low‐intrusiveness method to debug and optimize systems and processes. Low overhead is particularly important in embedded systems where resources and energy consumption is critical. The most advanced tracing infrastructures achieve a very low footprint on the traced software, bringing each tracepoint overhead to less than a microsecond. To reduce this still non‐negligible impact, the use of dedicated hardware resources is promising. In this paper, we propose complementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Table V is introduced by non-deterministic events (such as context switches). Verge et al [23] showed that an execution time overhead could occur if traces are stored in the ETB. In this work, as shown in Table V, the time overhead of CoreSight components is negligible for two main reasons.…”
Section: Implementation Resultsmentioning
confidence: 99%
“…Table V is introduced by non-deterministic events (such as context switches). Verge et al [23] showed that an execution time overhead could occur if traces are stored in the ETB. In this work, as shown in Table V, the time overhead of CoreSight components is negligible for two main reasons.…”
Section: Implementation Resultsmentioning
confidence: 99%
“…In the first part, we discuss the CPU-level tracing functionality designed for debugging and optimizing systems and processes 14 , as in analyzing bugs or crashes and checking control flow integrity for safe execution. Diverse research efforts have been made to analyze crashes and bugs [15][16][17][18][19][20] .…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, we used LTTng (Linux Tracing Toolkit Next Generation) [17] for sampling and collecting packet information from traffic. The details of collecting data from LTTng and modeling them at multiple levels to be used for advance attack analysis can be found at [32,29].…”
Section: Setup Configurationmentioning
confidence: 99%